Association between Handwashing Knowledge and Practices among the Students in Nepal - Sharma, Mohan Kumar; Khanal, Shanti Prasad; Acharya, Devaraj; Acharya, Jib (Prithvi Academic Journal, 2021)
Regular handwashing with soap and running water is one of the effective ways to stop spreading of germs that protects us from the disease. The aim of this study is to assess the handwashing knowledge and practice among the selected school students of Bardiya district in Nepal. To address this objective, the school-based descriptive cross-sectional design was applied. A total of 327 students including 9 to 12 grades were taken from four secondary schools using the multistage sampling technique. The validated self-administrated questionnaires were used to collect the data from the selected students. Similarly, the univariate (frequencies and percentage) and bivariate analyses (chi-square test for association) were performed to analyse the data, using the Statistical Package of Social Science (SPSS) 26 versions. Out of the total participants, 29.7% were between the ages of 15-16 years, 60.9% were male, and the majority (95.7%) were from Hindu. The study showed that 36.9% participants had the poor knowledge relating to handwashing. In contrast, it was found that 43.42% participants were found with the low practice of handwashing, which was higher than the knowledge level of handwashing. So having a good knowledge is not associated with good practices as regards to handwashing. It was noticed that the poor handwashing practice level remains higher as compared to the poor handwashing knowledge level. The study suggests that the schools have the responsibilities to give handwashing education to their students to raise the knowledge as well as the practice level of handwashing.